Apakah Tingkat Stres Berhubungan dengan Siklus Menstruasi pada Dewasa Muda : Is Stress Levels Related to Menstrual Cycles in Young Adults - Restiani, Ni Kadek Dwi Nanda; Sekarini, Ni Nyoman Ayu Desy; Pratiwi, Putu Irma (Indonesian Journal of Midwifery (IJM), 2026)
Regular menstruation is an important indicator of reproductive health because it reflects the balance of the hormonal system. Stress is one of the determinants that can affect the menstrual cycle. Midwifery students are a vulnerable group to experience stress due to academic demands and clinical practice. This study was conducted using a quantitative method using a cross-sectional approach. The study population consisted of female students of the D3 and S1 Midwifery study programs in the 2023-2025 intake. The study sample consisted of 158 respondents taken using a total sampling technique. Stress levels were measured using the Perceived Stress Scale (PSS-10) questionnaire, while menstrual cycles were categorized as normal and abnormal. Data analysis was performed using the chi-square test. The majority of respondents were in a state of moderate stress levels (80.4%) and had normal menstrual cycles (75.9%). The chi-square test results obtained a p-value of 0.489 (p > 0.05), which means there is no relationship between stress levels and menstrual cycles in midwifery students.. The stress levels experienced by most respondents were still within adaptive limits so they did not have a significant impact on the menstrual cycle. In addition, other factors such as body mass index (BMI), fatigue, lifestyle, and individual coping skills are confounding factors in influencing menstrual regularity. Stress levels are not significantly associated with menstrual regularity in midwifery students and are not the sole factor influencing menstrual regularity.   Abstrak Menstruasi yang teratur merupakan indikator penting dalam kesehatan reproduksi karena menggambarkan keseimbangan sistem hormonal. Stres menjadi salah satu determinan yang dapat mempengaruhi siklus menstruasi. Mahasiswa kebidanan menjadi kelompok rentan mengalami stres akibat tuntutan akademik dan praktik klinik. Studi ini dilakukan dengan metode kuantitatif menggunakan pendekatan cross-sectional. Populasi penelitian terdiri dari mahasiswi program studi D3 dan S1 Kebidanan angkatan 2023-2025. Sampel penelitian berjumlah 158 responden yang diambil menggunakan tenik total sampling. Pengukuran tingkat stres dilakukan menggunakan kuesioner Perceived Stress Scale (PSS-10), sedangkan siklus menstruasi dikategorikan menjadi normal dan tidak normal. Analisis data dilakukan menggunakan uji chi-square. Mayoritas responden berada dalam kondisi tingkat stres sedang (80,4%) dan memiliki siklus menstruasi normal (75,9%). Hasil uji chi-square diperoleh nilai p-value yaitu 0,489 (p > 0,05), yang artinya tidak terdapat hubungan antara tingkat stres dengan siklus menstruasi pada mahasiswa kebidanan. Tingkat stres yang dialami responden sebagian besar masih berada dalam batas adaptif sehingga belum berdampak signifikan terhadap siklus menstruasi. selain itu, terdapat faktor lain seperti indeks massa tubuh (IMT), kelelahan, pola hidup dan kemampuan coping individu yang menjadi faktor perancu dalam mempengaruhi keteraturan menstruasi. Tingkat stres tidak berhubungan secara signifikan dengan keteraturan menstruasi pada mahasiswa kebidanan dan bukan merupakan satu-satunya faktor yang mempengaruhi keteraturan menstruasi.